Behavioral evaluation of auditory function abnormalities in adult rats with normal hearing thresholds that were exposed to noise during early development - Rybalko, Natalia; Mitrovic, Dijana; Šuta, Daniel; Bureš, Zbyněk; Popelář, Jiří; Syka, Josef (Physiology & behavior, 2019)
Noise-exposed rat pups provide a model of early deprivation of sensory input to the central auditory system, allowing the study of developmental neuroplasticity. Our previous results have demonstrated that a brief exposure of rats to broadband noise (125 dB SPL 8 min, 14th postnatal day) at the onset of hearing resulted in an altered intensity perception and frequency discrimination in adulthood despite normal hearing thresholds. In this study, we assessed the gap-detection ability and possible presence of tinnitus- and hyperacusis-like behavior in adult rats after the same neonatal acoustic trauma, using measurements of the acoustic startle response (ASR) in quiet and noisy environments and its prepulse inhibition by gaps in noise (gap-PPI). A significant deficit in the ability to detect gap was observed in the exposed rats when 55 dB SPL broadband noise was used as background. An increase of noise intensity to 65-75 dB SPL led to strengthening of the gap-PPI in exposed animals, which approached the gap-PPI values of control animals at these levels. Behavioral signs of tinnitus (gap detection deficits in 10 kHz narrow band noise) were found in 25% of exposed rats. An increased sensitivity to continuous noise was manifested in all exposed rats by suppression of the ASR at significantly lower background noise levels than in the controls. This effect was particularly pronounced in rats with tinnitus-like behavior. Our results indicate that neonatal acoustic trauma, producing only a transient threshold shift, may produce permanent abnormalities in suprathreshold auditory functions and the development of tinnitus and hyperacusis-like behavior.
Keywords: úleková reakce; Hyperacusis; Animals; Auditory Threshold; Female; Acoustic trauma; nedoslýchavost z hluku; hyperakuze; ženské pohlaví; Hearing Disorders; Hearing Loss, Noise-Induced; Rats, Long-Evans; hluk; Tinnitus; chování zvířat; těhotenství; tinnitus; sluchový práh; potkani Long-Evans; Male; Rat; neuroplasticita; poruchy sluchu; krysa rodu Rattus; Behavior, Animal; Gap detection; Reflex, Startle; Acoustic startle; Neuronal Plasticity; zvířata; mužské pohlaví; Pregnancy; Noise; Rats